Assessing the performance of the 'Aquaculture Operation Phakisa Strategy' implementation from a stakeholder perspective - Halley, Keagan Desmond (Rhodes University, Faculty of Commerce, Rhodes Business School, 2019)
The global demand in aquatic products has seen a number of fisheries depleted worldwide through increase fishing pressure and over exploitation. South Africa in itself has 52 fisheries that are being exploited, of which 48% of these fisheries are of concern, either depleted or heavily depleted. Countries around world have now taken on the responsibility to reduce the reliance on capture fisheries and move towards a more sustainable form of ensuring fish supply. A stabilisation of fisheries stock worldwide has seen the rise of aquaculture as alternative activity that would contribute to reducing pressure on the global fisheries stocks while feeding the demand for fish protein. Aquaculture has since almost equaled the capture based fish supply, contributing to 44.1% of the world's total fisheries products in 2014 (FAO, 2016). Over the last few years the South African government has focused on developing the aquaculture sector through the development of strategies and policies. The most recent strategy launched in 2014 was Operation Phakisa: Unlocking the Economic Potential of South Africa's Oceans. The approach of Operation Phakisa looked at accelerating the delivery of government development priorities pertaining to the oceans economy, through development of plans and collaboration of delivery through all stakeholders (public and private stakeholders). Operation Phakisa methodology included bringing key stakeholders within academia, private and public sector, as well as civil society organisations to work together and develop strategies with clear targets that would drive the growth of their specific sectors. The year 2017 marked the midway point of the five year strategy implementation time frame, and an opportunity to assess the performance of the strategy implementation. In order to assess performance of the strategy implementation, the strategy implementation framework developed by Okumus (2003) was identified. Okumus (2003) identifies 11 implementation factors and categorizes these into four categories in the strategy implementation process, based on their role and characteristics, namely: Strategic Content (development of strategy), Strategic Context (internal and external context), Operational Process (operational planning, resource allocation, people, communication, and control) and Outcome (results of implementations process) (Okumus, 2003). The research involved the reviewing of documentation based on the strategy implementation as well as facilitated semi-structure interviews with two stakeholder groups. This was to gain an understanding from the stakeholders' perspective, on whether the Aquaculture Operation Phakisa Strategy (AOPS) is implemented according to Okumus (2003) Strategy Implementation Framework. Two stakeholder groups were interviewed, namely the officials implementing the strategy, and the aquaculture farmers being affected by the strategy implementation. The research found that eight of out of 11 factors from Okumus (2003) Strategy Implementation Framework were identified as being gaps within the implementation of the AOPS. These gaps were identified across all four main categories for strategy implementation (Strategic content, strategic context, operational process and outcomes). They included; strategy development, organisation structure, organisational culture, leadership, resource allocation, people, communication and outcomes. Furthermore, the researcher found that the perception from the officials differed to that of the aquaculture farmers, with the officials observing a more negative perception towards factors pertaining to organisational structure, organisational culture, leadership, resources allocated, people, communication and outcomes. This negative perception was experience towards the DAFF, Branch Fisheries Management as a whole, rather than within the officials own Chief Directorate (CD:AED), responsible for implementing the strategy. The research assisted with understanding the challenges affecting the implementation of the AOPS as well as unpacked strategy implementation in literature. This aided with developing recommendation to assist with enhancing strategy implementation performance of the AOPS. The following recommendation were provided: Change management within DAFF, Branch Fisheries Management; Identify responsible structures and personnel in DAFF, Branch Fisheries Management; Developing communication platforms within DAFF, Branch Fisheries Management; Review of outcomes of AOPS; and Ensure commitment from all at DAFF, Branch Fisheries Management (leadership). The research paper presents a simple method of assessing the strategy implementation process through the use of a strategy implementation framework.
Keywords: Marine resources -- Government policy -- South Africa; Fishery management -- South Africa; Aquaculture -- South Africa; Aquaculture industry -- South Africa; Operation Phakisa (South Africa)